2020
DOI: 10.5851/kosfa.2019.e93
|View full text |Cite
|
Sign up to set email alerts
|

Duck Oil-loaded Nanoemulsion Inhibits Senescence of Angiotensin II-treated Vascular Smooth Muscle Cells by Upregulating SIRT1

Abstract: Cellular senescence is associated with age-related vascular disorders and has been implicated in vascular dysfunctions. Here, we show that duck oil-loaded nanoemulsion (DO-NE) attenuates premature senescence of vascular smooth muscle cells (VSMCs) triggered by angiotensin II (Ang II). Compared with control nanoemulsion (NE), DO-NE significantly inhibited the activity of senescence-associated β-galactosidase, which is a biomarker of cellular senescence, in Ang II-treated VSMCs. SIRT1 protein expression was dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Later on, as DNs damage progress, the antioxidant capacity is reduced with the augmentation of oxidative stress injury (Qi et al 2018 ). It has been shown that SIRT1 prevents the development of endothelial dysfunction through attenuation progression of oxidative stress by multiple mechanisms including SIRT1/SOD, SIRT1/FOXO, SIRT1/eNOs, and SIRT1/NF-κB (Kang et al 2020 ). In addition, increasing ROS and oxidative stress by the aging process attenuate expression and functional activity of SIRT1 with further progress of oxidative stress and activation of inflammatory signaling pathway NF-κB leading to advanced inflammatory and oxidative stress injury (Bouchez and Devin 2019 ).…”
Section: Mechanistic Role Of Sirt1 In Pdmentioning
confidence: 99%
“…Later on, as DNs damage progress, the antioxidant capacity is reduced with the augmentation of oxidative stress injury (Qi et al 2018 ). It has been shown that SIRT1 prevents the development of endothelial dysfunction through attenuation progression of oxidative stress by multiple mechanisms including SIRT1/SOD, SIRT1/FOXO, SIRT1/eNOs, and SIRT1/NF-κB (Kang et al 2020 ). In addition, increasing ROS and oxidative stress by the aging process attenuate expression and functional activity of SIRT1 with further progress of oxidative stress and activation of inflammatory signaling pathway NF-κB leading to advanced inflammatory and oxidative stress injury (Bouchez and Devin 2019 ).…”
Section: Mechanistic Role Of Sirt1 In Pdmentioning
confidence: 99%
“…9 Numerous studies have demonstrated the potential of SIRT1 upregulation using both natural and synthetic compounds as a strategy for inhibiting cellular senescence and prolonging cellular longevity. 10,11 Dipeptidyl peptidase-4 (DPP)-4 is an exopeptidase enzyme expressed on the surface VSMCs that regulates glucagon-like peptide (GLP)-1 activity and has been shown to be involved in vascular flexibility. 12 GLP-1 is an incretin hormone secreted by intestinal L cells that activates the GLP-1 receptor (GLP-1R) to promote postprandial insulin secretion, among other functions.…”
Section: Introductionmentioning
confidence: 99%
“…Silent information-regulator 1 (SIRT1) is a NAD-dependent deacetylase that plays an important role in regulating the cell cycle by suppressing the acetylation of p53 protein . Numerous studies have demonstrated the potential of SIRT1 upregulation using both natural and synthetic compounds as a strategy for inhibiting cellular senescence and prolonging cellular longevity. , …”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1) is a member of the Sirtuin family of class III histone deacetylase enzymes, which plays a critical role in modulating cell senescence [ 6 ], cell proliferation [ 7 ], and inflammation responses [ 8 ]. Extensive studies have shown that SIRT1 overexpression protects human vessels against stress senescence of VSMCs stimulated by inflammation [ 9 , 10 ], thus improving the normal function of VSMCs, inhibiting vascular inflammation and plaque formation [ 3 ]. At the mechanistic level, p53 is a known senescence-promoting protein and is a downstream transcription factor regulated by SIRT1 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%